The Use of Fillers in Spoken Discourse Video by Students at English Language Education Study Program of State University of Gorontalo - Dhea Wulandari Cahyo; Hasanuddin Fatsah; Zulkifli Tanipu (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the Use of fillers in spoken discourse videos by students of the English Language Education Study Program at Gorontalo State University (UNG). The purpose is to identify the types of fillers used and the factors that influence their Use. This study uses a qualitative descriptive method with data collected through analysis of students' video assignments, interviews, and documentation. The results showed that the most frequently used fillers were unlexicalized (e.g., "um", "uh"), compared to lexicalized fillers (e.g., "so", "okay"). The main factors that influence the Use of fillers in spoken discourse video assignments are Inadequate preparation time, Divided attention, Filling the Void with Fillers, and Emphasis on Speaking. This study also revealed that fillers can be used in constructing sentences and maintaining fluency in communication even though they are considered to interfere with fluency. Pedagogical implications include teaching communication strategies to improve fluency and reducing excessive Use of fillers through speaking preparation and managing nervousness.